Introducing human geographies - Cloke, Paul J., 1953-; Crang, Phil, 1964-; Goodwin, Mark (Routledge, 2013)
"Introducing Human Geographies is the leading guide to human geography for undergraduate students. Written by expert international researchers, this thoroughly updated third edition explains new thinking on essential topics and discusses exciting developments in the field. Presented in three parts, it addresses the central ideas through which human geographers understand and shape their subject ('Foundations'), explores the main sub-disciplines from diverse angles ('Themes') and then looks to the future of human geography to assess the latest research in innovative areas ('Horizons'). Comprehensive, stimulating and cutting edge, Introducing Human Geographies, 3E, will be your essential guide"--Resumé vydavatele
Terminologický slovník
Keywords: geografie obyvatelstva; sociální geografie; kulturní geografie; human geography; cultural geography; příručky; handbooks, manuals, etc